Control of one stage bio ethanol production by recombinant strain (2007)
ABSTRACT: A new method for adaptive control of simultaneous saccharifi cation and fermentation of starch to ethanol by the recombinant strain Saccharomyces cerevisiae YPB–G is proposed. The process monitoring is enriched by new software sensors of glucose consumption and production rates. The difference between their values is defi ned as a control marker which is used for switching from batch to fed-batch mode automatically and for determining the amplitude and duration of starch feeding pulses (control input). Simulation results have shown that the proposed control strategy stabilizes the process at an equilibrium state for theglucose concentration. In this way, the ethanol concentration in the reactor and the productivity of the process are increased.